Green approaches for extraction, chemical modification and processing of marine polysaccharides for biomedical applications - Sacramento, Margarida M. A.; Borges, João; Correia, Fernando J. S.; Calado, Ricardo; Rodrigues, João M. M.; Patrício, Sónia G.; Mano, João F. (Frontiers in Bioengineering and Biotechnology, 2022)
Over the past few decades, natural-origin polysaccharides have received increasing attention across different fields of application, including biomedicine and biotechnology, because of their specific physicochemical and biological properties that have afforded the fabrication of a plethora of multifunctional devices for healthcare applications. More recently, marine raw materials from fisheries and aquaculture have emerged as a highly sustainable approach to convert marine biomass into added-value polysaccharides for human benefit. Nowadays, significant efforts have been made to combine such circular bio-based approach with cost-effective and environmentally-friendly technologies that enable the isolation of marine-origin polysaccharides up to the final construction of a biomedical device, thus developing an entirely sustainable pipeline. In this regard, the present review intends to provide an up-to-date outlook on the current green extraction methodologies of marine-origin polysaccharides and their molecular engineering toolbox for designing a multitude of biomaterial platforms for healthcare. Furthermore, we discuss how to foster circular bio-based approaches to pursue the further development of added-value biomedical devices, while the preserving the marine ecosystem.